Life Skill Psychoeducation Program using Academic-Experiential Approach for Indonesian Children in Hulu Kelang, Malaysia - Nur Amalia; Murfiah Dewi Wulandari; Junita Dwi Wardhani; Ana Fatwa Fauziyah; Milati Darmastuti; Fillah Ashar Nur Majid (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The basic skills of Indonesian children in the Hulu Kelang Learning Center (SB) are not comparable to school-age children and many children have not mastered basic literacy. Indonesian children at SB Hulu Kelang are children of migrant workers who were born and raised in Malaysia and they don't know their own nationality. This community service program is teaching practices and strengthens skills and character. Activities are carried out through an academic-experiential approach with a life skills program that includes intellectual skills, soft skills, and character by providing good practice. The methods used are observation methods, learning practices, community education, and advocacy. This service includes being creative, strengthening literacy and language, strengthening nationalism, and SECARA (a week of many events) which is carried out for one month. The results of this service show that psychoeducational service activities are needed to help Indonesian children to facilitate their academic abilities and character. The results of dedication have a positive impact on children and can improve literacy, nationalism, social life, and various basic skills needed for their future success.